CHEMICAL AND ORGANOLEPTIC PROPERTIES OF BEKAI (Pycnarrhena tumefacta Miers) LEAVES FOR FLAVOURING AGENT (BIO-VETSIN) - Rizki Maharani; Andrian Fernandes; Maman Turjaman; Harlinda Kuspradini; Ganis Lukmandaru (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2020)
The